THE CONTRIBUTIONS OF LITERACY SKILLS TO NATIONAL DEVELOPMENT - Vilya Lakstian Catra Mulia (UIN Raden Mas Said Surakarta, 2016)
Literacy refers to a set of skills for being literate of texts existing in society. There are many kinds of information penetrated among us. Being literate is now not only just represented by reading and writing as we simply do every day orthographically. It remains on basic literacy. This one itself has been improved for considering economic development by adding arithmetic skill. Literacy, with those language competences, considers its contribution for society in this modern age. It is considered as resource to reflect quality of each person. This functional literacy takes us for being functionally beneficial for surrounding environment.Â For dealing with the information around us which is massively spread, critical literacy should be optimized to make sense and take stance. In higher education context like university, scientific literacy is highly required to apply the subject for phenomena in the society. Along with types of literacy, how are their contributions on society? Being capable on multiple literacy levels is believed as the right way for familiarizing social phenomenon so that literate people have more chances to get possibilities for themselves up to strengthen citizen involvement for their nation as well. Literacy is finally constructed from optimizing each citizen on nationâ€™s development.